APPLICATION OF ROBOTIC TECHNOLOGY IN THE FASHION INDUSTRY - N. Yu. Barkova (Вестник университета)
Robotic technology as one of the factors that contribute to the economic growth of Russia has been considered in the article. The strengths and weaknesses, opportunities and threats of robotic technology development in Russia have been analysed. The advantages of use of robots in the fashion industry have been shown. The functioning of the robotic Adidas Speedfactory and some other factories that use in the production process of manufacturing goods of the fashion industry robotic systems, has been studied. The impact of robotic technology on supply chain management in the fashion industry has been assessed. The main reasons for possible changes in global supply chains in the fashion industry have been identified.